The impact of museumification to the local resident around Pasir Salak historical complex - Salleh, Khairul Syamil; Harun, Nor Zalina (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
With the enactment of Heritage Act in 2005, since then Malaysia had vigorously preserve and conserve any available heritage elements in the country. The act of museumification also had been conducted to preserve a historical site. However, not many gives attention to the impacts of the museumification to the local residents around the site area. Therefore, this research aims to provide an alternative solution to minimize the negative impacts and to enhance the positive impacts of museumification to the locals. The objectives of this research firstly is to study the definition of the museumification. Secondly, to identify the impacts of museumification from the local’s point of view. Lastly, it is to propose a design or alternative solutions for museumification of a village that minimize the negative impact and to enhance the positive impacts to the locals. The site chosen for this research is located at Pasir Salak Historical Complex in Pasir Salak, Perak. The data collection method chosen for this study is qualitative method involving interviews and observations. The data obtained from the interviews are divided into two parts. The first one is the impacts of museumification of the site in the early establishment which was in 1990 and the second one, the impacts on the present time which is 2017. The data shows that in 1990, 60 per cent of the residents feels negatively affected while the rest 40 per cent is positive. In 2017 the data change significantly giving 70 per cent of residents feels neutral about the museumification in their area while the rest is positively affected. Analysis made shows that the change of local resident perspective is due to the residents starting to feel used to the complex. It is also noted from the interview that visitors that visit the complex is not as many as before due to the lack of promotion on the historical complex. Thus, this paper will also discuss on the measures and the alternative suggestions to make the museumized complex more attractive to the outer visitors and at the same time to prevent the issues faced in the 1990 to repeat itself.